2018
DOI: 10.7554/elife.36245
|View full text |Cite
|
Sign up to set email alerts
|

The human leukemia virus HTLV-1 alters the structure and transcription of host chromatin in cis

Abstract: Chromatin looping controls gene expression by regulating promoter-enhancer contacts, the spread of epigenetic modifications, and the segregation of the genome into transcriptionally active and inactive compartments. We studied the impact on the structure and expression of host chromatin by the human retrovirus HTLV-1. We show that HTLV-1 disrupts host chromatin structure by forming loops between the provirus and the host genome; certain loops depend on the critical chromatin architectural protein CTCF, which w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 55 publications
4
67
1
2
Order By: Relevance
“…It has been reported that antisense proviral transcription is constitutively active, whereas sense transcription is frequently suppressed or expressed only intermittently. Previous studies also reported that transcription is regulated by genetic and epigenetic mechanisms [4750]; however, the findings of the current study indicate that there is another regulatory mechanism controlling proviral transcription at the post-transcriptional level.…”
Section: Discussioncontrasting
confidence: 76%
“…It has been reported that antisense proviral transcription is constitutively active, whereas sense transcription is frequently suppressed or expressed only intermittently. Previous studies also reported that transcription is regulated by genetic and epigenetic mechanisms [4750]; however, the findings of the current study indicate that there is another regulatory mechanism controlling proviral transcription at the post-transcriptional level.…”
Section: Discussioncontrasting
confidence: 76%
“…showed that integration of HTLV-1 and BLV preferentially occurs near cancer drivers and that insertional mutagenesis appears to drive the clonal persistence and expansion of transformed T cells 112 . All of these findings were supported by another recent publication 113 . In addition, Satou and Bangham et al .…”
Section: Pathogenic Mechanism Of Htlv-1 Diseasessupporting
confidence: 80%
“…For human T cell leukemia virus-1 (HTLV-1), long-range interactions between target gene promoters and viral enhancers are facilitated through chromatin looping utilizing the host zinc finger binding protein CTCF [62,63]. The HTLV-1 provirus contains a CTCF nucleotide-binding motif that has been shown to mediate clone-specific deregulation of host transcription from distances up to 300 kb [62], and CTCFmediated cis contacts within the host genome can be as far as 1.4 Mb [62,63]. Although M-MLV does not encode a known CTCF binding motif, CTCF binding sites have been identified at the promoter region of Rasgrp1 and~10 kb downstream from the integration site (ENCODE reference ENCFF310MUQ).…”
Section: Mechanisms Of Retroviral Enhancer Activationmentioning
confidence: 99%